The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12913-022-08354-y
|View full text |Cite
|
Sign up to set email alerts
|

Using a theory of change in monitoring, evaluating and steering scale-up of a district-level health management strengthening intervention in Ghana, Malawi, and Uganda – lessons from the PERFORM2Scale consortium

Abstract: Background Since 2017, PERFORM2Scale, a research consortium with partners from seven countries in Africa and Europe, has steered the implementation and scale-up of a district-level health management strengthening intervention in Ghana, Malawi and Uganda. This article presents PERFORM2Scale’s theory of change (ToC) and reflections upon and adaptations of the ToC over time. The article aims to contribute to understanding the benefits and challenges of using a ToC-based approach for monitoring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The emergent approach entails a dynamic, flexible or adaptable process that emerges from stakeholders’ interactions. We found that most CBP approaches were prescribed and collective,4 9 19 47 67 70 72 75–79 81 84 85 87 89–93 95–100 103 105 and prescribed and individual 17 68 69 71 73 80 82 83 86 94 101 102. The emergent and collective approach was marginal9 49 (figure 4).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The emergent approach entails a dynamic, flexible or adaptable process that emerges from stakeholders’ interactions. We found that most CBP approaches were prescribed and collective,4 9 19 47 67 70 72 75–79 81 84 85 87 89–93 95–100 103 105 and prescribed and individual 17 68 69 71 73 80 82 83 86 94 101 102. The emergent and collective approach was marginal9 49 (figure 4).…”
Section: Resultsmentioning
confidence: 91%
“…Weak leadership and/or management were considered the major causes of poor health outcomes in low-income and middle-income countries 4 6 19 49 67–88. Frequently mentioned causes of weak leadership and/or management capacity were (1) inadequate professional profiles of health managers (often being clinicians without formal training on leadership and management)17 73 75 81 89 90 and (2) inadequate efficacy of leadership and management courses (usually classroom-based and knowledge-focused instead of practice-based and providing know-how to deal with real-life situations) 47 68 69 73 74…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations